The complete sequence of the mitochondrial genome of Guanling pig (Sus scrofa). (3rd May 2016) - Ran, Mao-Liang; Yang, An-Qi; Li, Zhi; Chen, Bin
Abstract: Guanling pig is one of the native breeds in Guizhou Province in China. The compete mitochondrial genome of Guanling pig was determined by polymerase chain reaction (PCR). The result shows that the compete mitochondrial genome of Guanling pig is 16, 731 bp, and it contains a major non-coding control region (D-Loop region), 2 ribosomal RNA genes, 13 protein-coding genes (PCGs) and 22 transfer RNA genes. The mitochondrial DNA control region of the Guanling pig contains repeat motif TAC ACG TGC G, 5′ nucleotide of the first repeat is at the position 814 bp, and the repeat number is 13. The mitochondrial genome of Guanling pig subsequently provides important information in genetic mechanism and the evolution genomes.